2017
DOI: 10.2141/jpsa.0160122
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Analysis by Digital Camera for Separating Broiler Breast Meat with Low Water-Holding Capacity

Abstract: Separating breast meat with low water-holding capacity, conformation parameters (thickness, volume, bottom sarea, and perimeter), and color of chicken breast meat were measured by direct measurement and by imaging analysis with a digital camera. Samples were obtained from a production line. The L* value was used to separate the samples by three characteristics designating the quality of the meat: dark-colored samples (L*<50), normal-colored samples (50≤L*≤56), and light-colored samples (L*>56). Light-colored s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…Whilewater holding capacity (WHC) and pH values of raw chicken strips were 44.2 and 5.09 respectively. These results are in agreement with the data obtained by (Qiao,et al [13,28]). Total aerobic bacterial, coliform, E. coli, salmonella, staph.…”
supporting
confidence: 94%
“…Whilewater holding capacity (WHC) and pH values of raw chicken strips were 44.2 and 5.09 respectively. These results are in agreement with the data obtained by (Qiao,et al [13,28]). Total aerobic bacterial, coliform, E. coli, salmonella, staph.…”
supporting
confidence: 94%
“…Previous studies have confirmed that higher pH values are closely related to a lower drip loss and higher cooking loss, respectively [48]. It has elsewhere been reported that water-holding capacity has a high correlation with the L* value of breast muscle [49]. This correlation analysis is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with the data obtained [14,27]. Total aerobic bacterial, coliform, E. coli, salmonella, staph.…”
Section: Physicochemical and Microbiological Properties Of Raw Chicke...supporting
confidence: 92%